Upflow anaerobic sludge blanket reactor and biofilter in polyethylene as an alternative of decentralized wastewater treatment in municipality of Rio Rufino – SC - Souza, Diego Hoefling; Schroeder, Aline; Skoronski, Everton (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
Basic sanitation services are essential for promoting public health and for mitigating environmental damage. Thus, the objective of this work was to evaluate a wastewater treatment system consisting of anaerobic sludge blanket reactor and biofilter, as an alternative for the decentralized wastewater treatment in the municipality of Rio Rufino - Santa Catarina. The system was evaluated for its efficiency of removal of fecal coliforms, biochemical oxygen demand, chemical oxygen demand, soluble chemical oxygen demand, phosphorus, Total Kjhedal Nitrogen, nitrite, nitrate, sedimentable solids and maintenance of the hydrogen potential in the effluent. The treated effluent had its parameters compared to the standards established by Resolution 430/2011 of the Conselho Nacional do Meio Ambiente and Law 14.675 / 2009 of the State of Santa Catarina. It was also performed the estimate of the daily biochemical oxygen demand load, originated by the population of the municipality, and its respective impact. The effluent treated by the proposed system, when properly installed, follows what was established by the legislation, which implies in reducing the impacts caused by the municipality. In this way, the system can be an interesting alternative when it comes to decentralized wastewater treatment.